2021
DOI: 10.1038/s41565-021-00994-1
|View full text |Cite
|
Sign up to set email alerts
|

Quantum-coherent nanoscience

Abstract: For the past three decades, nanoscience has widely affected many areas in physics, chemistry, and engineering, and has led to numerous fundamental discoveries as well as applications and products.Concurrently, quantum science and technology has developed into a cross-disciplinary research endeavour connecting these same areas and holds a burgeoning commercial promise. Although quantum physics dictates the behaviour of nanoscale objects, quantum coherence, which is central to quantum information, communication … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
112
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

5
5

Authors

Journals

citations
Cited by 116 publications
(115 citation statements)
references
References 132 publications
(169 reference statements)
3
112
0
Order By: Relevance
“…However, by slightly increasing the thickness of the molecular film, we detected the retention of the SCO behaviour. This paves the way for the chemical modification of the TTF ligand to avoid the ion-surface interaction, making this system attractive for the development of a molecular-based spintronic device [44].…”
Section: Discussionmentioning
confidence: 99%
“…However, by slightly increasing the thickness of the molecular film, we detected the retention of the SCO behaviour. This paves the way for the chemical modification of the TTF ligand to avoid the ion-surface interaction, making this system attractive for the development of a molecular-based spintronic device [44].…”
Section: Discussionmentioning
confidence: 99%
“…The design of magnetic molecules able to retain the direction of their magnetic moment for long times [4], commonly known as single-molecule magnets, has been one of the central goals for a large community of chemists, physicists and material scientists for a long time [5]. More recently, the advent of disciplines such as spintronics [6][7][8] and quantum science [9][10][11][12][13] have also attracted the attention of the molecular magnetism community. For instance, it has been experimentally demonstrated that molecules can be embedded in solid-state spintronics [14] devices to influence the flow of currents [15].…”
Section: Introductionmentioning
confidence: 99%
“…Physical realizations of solid-state spin systems include gate-defined quantum dots, single dopants in semiconductors such as phosphorus donors in silicon, and single defects in insulators such as nitrogen-vacancy centers in diamond [5,6,7]. Harnessing quantum resources at the nanoscale gives birth to the discipline of quantum-coherent nanoscience that may bring forth useful quantum nanodevices "at the bottom" [8,9].…”
Section: Introductionmentioning
confidence: 99%